HARMONIOUS RELATIONSHIP BETWEEN ISLAM AND SCIENCE IN THE PERSPECTIVE OF THE QUR'AN - Lalu Pattimura Farhan (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2023)
This article discusses the views of the scholars of exegesis on a number of verses related to the relationship between Islam and science (science). This article departs from an article entitled “Islam can give a proper orientation to science and technology development